THE ROOT CAUSES AND NEXUS OF MILITANT ISLAMIC MOVEMENTS IN INDONESIA: CASE STUDIES OF DARUL ISLAM AND JEMAAH ISLAMIYAH - Sri Yunanto; Angel Damayanti (Kajian Asia Pasifik, 2017)
Many scholars believe that every religion has its peaceful interpretation as well as violent practices. Yet, this article elaborates more on the Islamic radical movements in Indonesia, particularly on the questions of what factors have triggered them to conduct such violence, how they linked each other and what action should be taken by the Indonesian government to counter-terrorism. To answer the question, the paper will focus on the ideology part and organization network of Darul Islam (DI) and Jemaah Islamiyah (JI), which shared similar ideology, network and methods of recruitment. Authors argue that ideology and organization become vital elements for DI and JI, in which the government, coupled with all stakeholders, should pay more attention if they want to eradicate violence in the name of religion. Although there is â€œno prescription fits allâ€ in eradicating terrorism, the ability to understand the root causes and organization network of terrorism in Indonesia will help the government and all stakeholders to establish a proper strategy. Key words: Counter-terrorism, salafi jihadism, Darul Islam, Jemaah Islamiyah Abstrak Banyak pengamat percaya bahwa setiap agama mengandung interpretasi damai sekaligus juga tindak kekerasan. Namun, artikel ini akan mengulas lebih banyak tentang gerakan radikal Islam di Indonesia, terutama yang terkait dengan faktor-faktor apa saja yang mendorong mereka melakukan aksi kekerasan, bagaimana kelompok-kelompok tersebut saling memiliki keterkaitan dan tindakan apa yang perlu diambil oleh pemerintah Indonesia dalam melakukan kontra-terorisme. Untuk menjawab pertanyaan tersebut, paper ini akan menjelaskan ideologi dan jaringan organisasi dari Darul Islam (DI) dan Jemaah Islamiyah (JI), di mana keduanya memiliki kemiripan termasuk juga dalam metode rekrutmen. Penulis berpendapat bahwa ideologi dan organisasi merupakan elemen penting bagi DI dan JI. Oleh karena itu, pemerintah dan seluruh elemen masyarakat harus memperhatikan hal ini jika ingin memberantas kekerasan atas nama agama. Walaupun tidak ada â€œresep ampuhâ€ yang dapat mengatasi terorisme, kemampuan untuk memahami akar permasalahan dan jaringan organisasi kelompok terorisme di Indonesia akan membantu pemerintah dan seluruh elemen masyarakat untuk menyusun strategi yang tepat. Kata Kunci: Counter-terrorism, salafi jihadisme, Darul Islam, Jemaah Islamiyah